The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1038/s41467-021-21457-0
|View full text |Cite
|
Sign up to set email alerts
|

Network models of primary melanoma microenvironments identify key melanoma regulators underlying prognosis

Abstract: Melanoma is the most lethal skin malignancy, driven by genetic and epigenetic alterations in the complex tumour microenvironment. While large-scale molecular profiling of melanoma has identified molecular signatures associated with melanoma progression, comprehensive systems-level modeling remains elusive. This study builds up predictive gene network models of molecular alterations in primary melanoma by integrating large-scale bulk-based multi-omic and single-cell transcriptomic data. Incorporating clinical, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 88 publications
(90 reference statements)
0
27
0
Order By: Relevance
“…A prior study reported that liver metastasis induced tumor-specific CD8 + T cell loss in preclinical models, which mirror the systemic CD8 + T cell loss and reduced immunotherapy efficacy observed in patients with liver metastasis [ 24 ]. High CD8 + T cells immune infiltration is found to be correlated with a good prognosis in melanoma [ 25 ]. The high density of direct CD8 + T/B cell interactions also can predict patients with an excellent prognosis, who would receive less invasive treatment in oropharyngeal squamous cell carcinoma [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…A prior study reported that liver metastasis induced tumor-specific CD8 + T cell loss in preclinical models, which mirror the systemic CD8 + T cell loss and reduced immunotherapy efficacy observed in patients with liver metastasis [ 24 ]. High CD8 + T cells immune infiltration is found to be correlated with a good prognosis in melanoma [ 25 ]. The high density of direct CD8 + T/B cell interactions also can predict patients with an excellent prognosis, who would receive less invasive treatment in oropharyngeal squamous cell carcinoma [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…We constructed gene co-expression networks from normalized and covariate-adjusted gene expression data. As age may influence senescence geneexpression, we constructed two sets of gene co-expression networks through the established multiscale gene co-expression network analysis (MEGENA) [ 27 30 ], one based on the data adjusted for age and the other from the data without age adjustment. Briefly, Pearson correlation coefficients (PCCs) were computed for all gene pairs.…”
Section: Methodsmentioning
confidence: 99%
“…The in vivo expression patterns of SnGs across multiple human tissues remain unknown, and the cell-type specific molecular signatures of cellular senescence have not been revealed. In this study, we applied our previously established system biology approach [ 27 30 ] to identify co-expressed networks of SnGs in 50 non-diseased human tissues. We identified co-expression structures of SnGs and constructed a consensus senescence network conserved across multiple healthy tissues.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, single-cell techniques have been applied in identifying biomarkers to predict prognosis of cancer patients. For instance, by integrating large-scale bulk multi-omics and single-cell transcriptomic data of primary melanoma, a predictive model was constructed and 17 genes associated with the poor prognosis of patients were identified (Song et al, 2021). Finally, single-cell sequencing has been used to reveal the prognostic roles of stromal cell heterogeneity in multiple Cancers (Savas et al, 2018;Dominguez et al, 2020;Gong et al, 2021).…”
Section: Single-cell Multi-omics and Precision Cancer Therapymentioning
confidence: 99%